The Use of Coal Gangue as a Cultivation Bed Conditioner in Forage Maize Inoculated with Arbuscular Mycorrhizal Fungi. Issue 11 (17th June 2017) - Motesharezadeh, Babak; Ahmadiyan, Elaheh; Alikhani, Hossein Ali; Azarnivand, Hossein
ABSTRACT: A greenhouse pot experiment was conducted to investigate the effect of application of coal gangue (CG) at different rates (0, 5, 10, 20, and 50%) and inoculation with two arbuscular mycorrhizal (AM) fungi Glomus intraradices and Glomus mosseae, as mediating plant adaptation to soil amended with CG, on the nutrient content of forage maize. The results showed CG amendment at all levels and both AM fungi significantly improved the nutrient content of the plant as compared to control. In general, the highest shoot dry weight and nutrient phosphorus, iron, and zinc (P, Fe, and Zn) were obtained with 10% CG and G. intraradice treatments, which were 49.68, 30.49, 16.72, and 75.71% higher than those of the control plants, respectively. Therefore, 10% dose of CG may be considered as a suitable dose for amendment in the corn cultivation bed in terms of providing nutrient contents for this plant as well as AM fungi root colonization.